Promising response of proliferative glomerulonephritis with monoclonal IgG deposits to low-dose daratumumab: a case report - Xu, Hongyao; Huang, Yao; Dong, Ling; Yu, Hua; Lin, Bo (Frontiers in Medicine, 2024)
Proliferative glomerulonephritis with monoclonal immunoglobulin deposits (PGNMID) is a rare disease without standardized treatment modalities. Daratumumab is a human IgG monoclonal anti-CD38 antibody that has been demonstrated to be highly effective and safe in the treatment of PGNMID. This article reports a 66-year-old female who suffered from edema in both lower limbs and face for six years with mild proteinuria and hypoproteinemia. Renal biopsy displayed eight glomeruli, among which two presented with glomerulosclerosis, and the remaining six exhibited moderate diffuse hyperplasia of glomerular mesangial cells and stroma with endothelial cell proliferation. Immunofluorescence microscopy revealed lumpy and diffuse deposits of C3, C1q, IgG, and κ light chain in the glomerular mesangium, with strongly positive staining for IgG3 and varying degrees of weak to negative staining for IgG1, IgG2, IgG4, and λ light chain. Additionally, ultrastructural analysis unveiled that the glomerular basement membrane was segmentally thickened, accompanied by diffuse pedicle fusion, segmental tethered insertion, subendothelial deposits, and electron-dense material in tethered areas. The patient received a total dose of 800 mg of daratumumab (400 mg daily for two consecutive days), as well as daily prednisone (25 mg) and valsartan (80 mg), for treatment and achieved complete remission after three-month follow-up. This case represents an early attempt to treat PGNMID with low-dose daratumumab but requires long-term follow-up.